LOZENGES FORMULATION OF CIPLUKAN (PHYSALIS ANGULATA L.) FRUIT EXTRACT AS AN ANTIOXIDANT WITH COMBINATION OF FILLER AGENTS AVICEL PH 102–LUDIPRESS - TANJUNG, YENNI PUSPITA; AKMAL, TUBAGUS; JULIANTI, ANDI IKA; FAUZIYYAH, AMANINA; RIKI, APEP (International Journal of Applied Pharmaceutics, 2023)
Objective: This research aimed to determine the effect of variations in the concentration of filler agents Avicel PH 102-Ludipress on the evaluation results of granules and tablets and to determine the antioxidant activity of ciplukan (Physalis angulata L.) fruit extract lozenges. Methods: The extract was obtained by the soxhletation method using ethanol 96%. The lozenges were made by direct compression, and the formula was divided into 3 concentration variations of Avicel PH 102 and Ludipress, namely F1 (1:2), F2 (1:1), and F3 (2:1). The best lozenges were tested for their antioxidant activity using the DPPH method. Results: The results of statistical analysis using the One Way Anova test formulation of ciplukan fruit extract lozenges with variations in concentrations of Avicel PH 102 and Ludipress had a significant effect (p<0.05) on the angle of repose, bulk density, tapped density, Carr's index, Hausner's ratio, thickness, friability, and disintegration time, but no significant effect (p>0.05) on diameter, weight variation, and hardness. The best ciplukan fruit extract (F1) lozenge formula has a concentration ratio of Avicel PH 102 and Ludipress (1:2) with an IC50 value of 28.46 ppm and is classified as a very strong antioxidant. Conclusion: Ciplukan fruit extract formulated in the form of lozenges with varying concentrations of the filler Avicel PH 102: Ludipress (1:2) has very strong antioxidant activity.